1974
DOI: 10.1128/aem.28.3.489-497.1974
|View full text |Cite
|
Sign up to set email alerts
|

Sulfate Reduction by a Desulfovibrio Species Isolated from Sheep Rumen1

Abstract: Several dissimilatory, sulfate-reducing bacteria were isolated from the rumen fluid of sheep fed purified diets containing sulfate. One isolate, strain D, was selected for characterization. This organism is a nonsporeforming, obligately anaerobic, mesophilic, nonmotile, gram-negative, straight rod. Cell-free extracts show absorption maxima for cytochrome c3 and desulfoviridin, characteristic of Desulfovibrio. Carbohydrates, as a sole carbon source, will support growth. Lactate supports growth in the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

1980
1980
2019
2019

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 23 publications
1
24
0
Order By: Relevance
“…This premise is consistent with a previous study where the addition of nitrate had a stimulatory effect on the subsequent reduction in sulphate (Sørensen 1982). Decreased sulphide concentration in the presence of ferric citrate, alone and in combination, was consistent with our previous report (Wu et al 2016), and it can be explained, at least partially, by the ability of Desulfovibrio spp., which was reported as the prevalent SRB in the rumen, to reduce ferric iron (Huisingh et al 1974). Drewnoski et al (2014) also reported a decrease in H 2 S gas production in the rumen of beef cattle when ferric citrate was added to the diet.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This premise is consistent with a previous study where the addition of nitrate had a stimulatory effect on the subsequent reduction in sulphate (Sørensen 1982). Decreased sulphide concentration in the presence of ferric citrate, alone and in combination, was consistent with our previous report (Wu et al 2016), and it can be explained, at least partially, by the ability of Desulfovibrio spp., which was reported as the prevalent SRB in the rumen, to reduce ferric iron (Huisingh et al 1974). Drewnoski et al (2014) also reported a decrease in H 2 S gas production in the rumen of beef cattle when ferric citrate was added to the diet.…”
Section: Discussionmentioning
confidence: 93%
“…The genus Desulfovibrio was reported as the prevalent SRB in the rumen, and some species of this genus could reduce ferric iron (Huisingh et al 1974). Thus, the abundance of Desulfovibrio was quantified to evaluate the effect of the three inhibitors on this genus.…”
Section: Discussionmentioning
confidence: 99%
“…They establish very early after birth in the rumen of lambs raised under conventional conditions [4,5], in parallel with cellulolytic bacteria. Among the other microbial groups capable of hydrogen utilization, sulfate-reducing bacteria have been reported from the rumen of sheep and cattle, while acetogenic bacteria were isolated from the rumen of steers [6][7][8][9]. The aim of the present work was to follow the establishment of the different H2-utilizing bacteria in the rumen microflora of newborn lambs.…”
Section: Introductionmentioning
confidence: 96%
“…However, anomalous strains have been reported in the literature over this period [e.g. 2,3,5,12,[15][16][17][18]. Some reservations on the present system have been expressed by Postgate [1,5].…”
Section: Biochemical Characteristicsmentioning
confidence: 99%